Complete genome sequence of Cryptobacterium curtum type strain (12-3T). Issue 2 (September 2009) - Mavrommatis, Konstantinos; Pukall, Rüdiger; Rohde, Christine; Chen, Feng; Sims, David; Brettin, Thomas; Kuske, Cheryl; Detter, John; Han, Cliff; Lapidus, Alla; Copeland, Alex; Glavina Del Rio, Tijana; et al.
Abstract Cryptobacterium curtum Nakazawaet al. 1999 is the type species of the genus, and is of phylogenetic interest because of its very distant and isolated position within the familyCoriobacteriaceae .C. curtum is an asaccharolytic, opportunistic pathogen with a typical occurrence in the oral cavity, involved in dental and oral infections like periodontitis, inflammations and abscesses. Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first complete genome sequence of the actinobacterial familyCoriobacteriaceae, and this 1, 617, 804 bp long single replicon genome with its 1364 protein-coding and 58 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.